USABILITY EVALUATION OF A DESKTOP VIRTUAL REALITY PROTOTYPE (DVRP) COURSEWARE TO ENHANCE KNOWLEDGE ON DRUG ABUSE - Hashim, Ameer Fuhaili Mohamad; Hussin, Huzili; Othman, Mohamad Hashim; Syed Ahmad, Sharifah Amnah (Journal of Techno-Social, 2016)
Evaluation is a way to measure the usability of a computer-based system. Usability is the ability to carry out tasks effectively, efficiently and with satisfaction. Usability is the extent to which users can use a computer system to achieve specified goals effectively and efficiently while promoting feelings of satisfaction in a given context of use. It can be broadly defined as â€œease of useâ€, and â€œusefulnessâ€. This study aims to evaluate the usability, of the Desktop Virtual Reality Prototype (DVRP) courseware in enhancing knowledge on drug abuse among student teachers in a Teacher Education Institution. A total of 35 student-teachers were identified through simple random method to evaluate the usability of DVRP. In order to assess the usability of the DVRP courseware, the USE Questionnaire (Lund, 2001) was employed. USE stands for Usefulness, Satisfaction, and Ease of use. The results of this study on the usability show that the uses are very positive using the DVRP courseware and very effective and efficient to be used to enhance knowledge on drug abuse.